3 Southeast Asian Governments’ Initial Crisis Rhetoric during the Covid-19 Pandemic in Online News - Indiyati, Diyah; Ghazali, Akmar Hayati Ahmad; Yohanes, Yulanda Trisula Sidarta; Chotijah, Siti (Universitas Semarang, 2023)
Introduction: Governmental responses to the pandemic vary by country. This study seeks to evaluate the Government's preliminary crisis rhetoric by employing a framing typology frequently utilised in Public Relations as reported in mass media across Indonesia, Malaysia, and Singapore. This study examines articles regarding government narratives published from January to March 2020 in Detik.com, Straitstimes.com, and Thestar.com. A total of 22.338 news reports about the pandemic were retrieved from the respective media. The three media was selected due to its national reach and readership. Methods: This paper employs qualitative-thematic and content analysis to analyze the materials collected from internet news sources. The study was conducted systematically, involving several steps. A thematic analysis was performed on the government messages to reveal governments’ initial crisis intersecting concept of crisis rhetoric and framing typology in PR. Findings: The Indonesian Government adopted the rhetorical appeal of ‘kairos’, ‘ethos’, and ‘pathos’ as means of persuasion to build the frame of choice and issues in the messages to the public. The Malaysian Government exhibited ‘ethos’ and ‘pathos’ appeal to build frame of responsibility and action in the messages carried out by the Government in the mass media. Meanwhile, the Singapore government uses the rhetorical appeal of ‘logos’ and ‘ethos’ in creating frame of action, responsibility, and situations that exist in the news covering government statements from Singapore. Originality: Studies linking framing with rhetoric are scarce, mostly framing analysis focusing more on the journalist activities in constructing the frame within the news.